2021
DOI: 10.1186/s13071-021-04819-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Crimean-Congo hemorrhagic fever virus in blood-fed Hyalomma ticks collected from Mauritanian livestock

Abstract: Background Crimean-Congo hemorrhagic fever virus (CCHFV) belongs to the genus Orthonairovirus (Nairovididae) and is a (re)emerging tick-borne pathogen. It is endemic in most parts of Africa, Asia and southern Europe, and can cause severe hemorrhagic symptoms in humans, with high fatality rates (5–30%). Methods Hyalomma ticks were collected from four different livestock herds (cattle and camels) in Mauritania in 2018. The tick species were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Indeed, Hyalomma marginatum is the most studied and known vector of CCHFV in Europe and Asia where it is responsible of the transovarian and transstadial transmission of the virus, ensuring, therefore, its maintenance in nature ( Spengler et al., 2016 ). In Africa, the virus has been detected on numerous occasions in H. dromedarii, H. truncatum, H. rufipes and H. impeltatum ( Swanepoel et al., 1983 ; Zivcec et al., 2017 ; Chitimia-Dobler et al., 2019 ; Kajihara et al., 2021 ; Schulz et al., 2021 ) but also in non Hyalomma species ( Lule et al., 2022 ). In our study, CCHFV was found in H. truncatum , although at a low infection rate but not in H. rufipes , H. impeltatum , H. nitidum, H. detritum , and H. dromaderii.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Hyalomma marginatum is the most studied and known vector of CCHFV in Europe and Asia where it is responsible of the transovarian and transstadial transmission of the virus, ensuring, therefore, its maintenance in nature ( Spengler et al., 2016 ). In Africa, the virus has been detected on numerous occasions in H. dromedarii, H. truncatum, H. rufipes and H. impeltatum ( Swanepoel et al., 1983 ; Zivcec et al., 2017 ; Chitimia-Dobler et al., 2019 ; Kajihara et al., 2021 ; Schulz et al., 2021 ) but also in non Hyalomma species ( Lule et al., 2022 ). In our study, CCHFV was found in H. truncatum , although at a low infection rate but not in H. rufipes , H. impeltatum , H. nitidum, H. detritum , and H. dromaderii.…”
Section: Discussionmentioning
confidence: 99%
“…Between February and May 2022, 8 patients were admitted to Centre Hospitalier de Kiffa (Kiffa department/Assaba region), Hôpital Hamed (Boutilimit department/Trarza region), Centre Hospitalier Cheikh Zeid, Centre Hospitalier National de Nouakchott, or Hôpital de l’Amitié (Nouakchott) with an initial clinical diagnosis of CCHF. This period of the year is characterized by a hot, dry season and transhumance of livestock, which favors the spread of ticks [ 11 , 14 ]. The study population of the present study was individuals who were potentially in contact with these 8 patients suspected to be infected with CCHFV.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies conducted in Africa and Asia have shown that CCHF seroprevalence significantly increases with the animal age, either in cattle, small ruminants, and camels (33,35,(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97). This correlation was mainly attributed to an increasing probability of an animal to be exposed to infected tick vectors, contract CCHFV, and develop an immune response in relation with increasing age (33).…”
Section: Factors That May Promote Cchfv Enzootic Transmission In Fran...mentioning
confidence: 99%
“…In Sudan, when assessing age as a risk factor for cattle CCHFV seroprevalence, the authors showed that calves started to get infected after the age of 2 years, as this was when animals were released to pasture and therefore became exposed to infected ticks and subsequently to CCHFV infection ( 35 , 89 ). In Mauritania, this hypothesis of overexposure in older animals has been also proposed to explain an apparent higher seroprevalence in camels than in cattle or small ruminants, as camels are bred for longer periods of time ( 95 ). Although we agree that the age effect may be a confounding factor with animal species, most ticks present host preferences that could result in differential infestation rates according to the vertebrate species.…”
Section: Factors That May Promote Cchfv Enzootic Transmission In Fran...mentioning
confidence: 99%